2007
DOI: 10.1093/ndt/gfl783
|View full text |Cite
|
Sign up to set email alerts
|

Effect of haemodiafiltration with online regeneration of ultrafiltrate on oxidative stress in dialysis patients

Abstract: The results of our study indicate that HFR treatment, compared with standard dialysis, has a lower impact on OxSt. Given, the strong relationship between OxSt and inflammation and their impact on the long-term cardiovascular complications in end-stage renal disease patients, HFR might have a more beneficial impact in reducing the risk of atherosclerotic cardiovascular disease in dialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
2
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 29 publications
8
49
2
2
Order By: Relevance
“…It has also been shown that online HDF reduces the circulating levels of AGEs that are considered as markers of oxidative stress and are putatively implicated in the dialysis-related complications of long-term dialysis patients (β 2 M amyloidosis and atherosclerosis) [39]. A variation of online HDF, HDF with online regeneration of ultrafiltrate, which combines the processes of diffusion, convection and absorbance, appears in recent well-designed studies to reduce levels of cytokines such as IL-6 and CRP and to have a positive impact on oxidative stress as well, compared with standard dialysis [42,43,44]. In addition, both methods were shown to be superior compared to standard bicarbonate HD in reducing the inflammatory state of dialysis patients [43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that online HDF reduces the circulating levels of AGEs that are considered as markers of oxidative stress and are putatively implicated in the dialysis-related complications of long-term dialysis patients (β 2 M amyloidosis and atherosclerosis) [39]. A variation of online HDF, HDF with online regeneration of ultrafiltrate, which combines the processes of diffusion, convection and absorbance, appears in recent well-designed studies to reduce levels of cytokines such as IL-6 and CRP and to have a positive impact on oxidative stress as well, compared with standard dialysis [42,43,44]. In addition, both methods were shown to be superior compared to standard bicarbonate HD in reducing the inflammatory state of dialysis patients [43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…76,77 Similarly, adsorption can be combined with diffusion when used for dialysis against dialysate containing lipophilic elements 78 or albumin. 79 Adsorption of spent peritoneal dialysate, with reinfusion into the peritoneal cavity, may be another diffusive/adsorptive approach that has the advantage of eliminating biocompatibility reactions with blood constituents.…”
Section: Current Situationmentioning
confidence: 99%
“…Recientemente están apareciendo nuevas técnicas convectivas como la hemodiafiltración con reinfusión endó-gena (HFR), que por su diseño podría mejorar los resultados de la HDF-OL [7][8][9] . En esta técnica, el líquido de reposición utilizado es el mismo que previamente se ha ultrafiltrado, el cual se infunde en el circuito hemático una vez regenerado al hacerlo pasar por un cartucho que contiene una resina adsortiva en el que quedan adheridas las toxinas urémicas.…”
Section: Methodsunclassified